How we understand obstetric violence - Távara-Orozco, Luis (2024)
What is called obstetric violence we prefer to call institutional violence against womenduring obstetric care, mainly to avoid stigmatization of professionals. Research hasbeen carried out worldwide on its occurrence, although in Latin America there islimited information from fieldwork. There is still no agreed definition at the level ofhealth or medical organizations, and different names have been adopted to defineit. Its etiology is multifactorial, and its consequences are physical, mental and sexual,and in extreme cases it can lead to maternal and/or perinatal death. This sectionreviews the different components of this type of violence and the measures adoptedto control its occurrence.